The impact of breast reconstruction on the quality of life of women after mastectomy - Rzońca, Agnieszka; Fronczak, Adam (Journal of Education, Health and Sport, 2017)
Introduction: Breast cancer is the most common tumor among women. The treatment of breast cancer is becoming increasingly less mutilating but in many cases it requires drastic surgical procedures. Brest cancer imposes a significant psychological strain on woman. : Breast reconstruction is an element of complex treatment of breast cancer which can improve the quality of life for women. Aim: The aim of the present study was to demonstrate the impact of breast reconstruction on the quality of life for women after mastectomy procedure. Material and methods. The survey was conducted among 92 women belonging to the Amazon association. Breast reconstruction has been used on 46 women. The author's questionnaire is used to assess the quality of life. Results: The largest group of respondents were women over 55 years of age. More than half of the respondents had children. 80% of the women were satisfied with the effects of the re construction. The most common changes that triggered the reconstruction were improvement of mood, improvement of appearance and increased self-confidence.